2020
DOI: 10.1162/jocn_a_01545
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Underpinnings of Aggressive Predation in Economic Contests

Abstract: Competitions are part and parcel of daily life and require people to invest time and energy to gain advantage over others and to avoid (the risk of) falling behind. Whereas the behavioral mechanisms underlying competition are well documented, its neurocognitive underpinnings remain poorly understood. We addressed this using neuroimaging and computational modeling of individual investment decisions aimed at exploiting one's counterpart (“attack”) or at protecting against exploitation by one's counterpart (“defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Some studies in political psychology also suggest that a rigid cognitive style and low 'need for cognition' are more prevalent among those endorsing rightist rather than leftist ideologies [10,12,17]. We showed that sophisticated reasoning and perspective taking modulate the aggressiveness of attack, but not defence [60][61][62]. If adhering to conservative ideology is associated with cognitive rigidity more than endorsing liberal ideology, one would expect reactionaries to be relatively more aggressive attackers than progressives, and defence to not differ between modernists and conservatists.…”
Section: Political Ideology and Games Of Attack And Defencementioning
confidence: 51%
See 4 more Smart Citations
“…Some studies in political psychology also suggest that a rigid cognitive style and low 'need for cognition' are more prevalent among those endorsing rightist rather than leftist ideologies [10,12,17]. We showed that sophisticated reasoning and perspective taking modulate the aggressiveness of attack, but not defence [60][61][62]. If adhering to conservative ideology is associated with cognitive rigidity more than endorsing liberal ideology, one would expect reactionaries to be relatively more aggressive attackers than progressives, and defence to not differ between modernists and conservatists.…”
Section: Political Ideology and Games Of Attack And Defencementioning
confidence: 51%
“…Typically, compared with defence, investments in attack are less frequent and lower overall, yet investments in both attack and defence substantially exceed equilibrium levels: with an endowment of e = 10, investments greater than 6 should never occur theoretically yet are frequently observed in laboratory experiments (figure 2a,b). Because conflict intensity is higher, attackers and defenders earn less than predicted (figure 2c), and collective welfare is reduced more than would be expected under rational-choice theory (figure 2d ) [59][60][61][62]. Rational-choice theory is traditionally premised on the threefold assumption that people (i) hold selfish preferences, (ii) have unlimited information processing capacity, and (iii) assume selfishness and unlimited processing capacity in others.…”
Section: Neurocognitive Mechanisms Of Attack and Defencementioning
confidence: 99%
See 3 more Smart Citations